Infant and young child feeding practices differ by ethnicity of Vietnamese mothers - Nguyen, Tuan T.; Nguyen, Phuong Hong; Hajeebhoy, Nemat; Nguyen, Huan V.; Frongillo, Edward A. (Springer, 2016)
Limited studies have examined ethnic variation in breastfeeding and complementary feeding practices in developing countries. This study investigated ethnic variation in feeding practices in mothers with children 0–23 months old in Vietnam. We used data on 1875 women who came from the ethnic majority, Kinh (n = 989, randomly sampled from 9875 surveyed Kinh mothers, 10 % from each province) and three ethnic minorities: E De-Mnong (n = 309), Thai-Muong (n = 229) and Tay-Nung (n = 348). Ethnic minorities were compared with the Kinh group using logistic regression model. Prevalence of breastfeeding initiation within an hour of birth was 69 % in Thai-Muong, but ~50 % in other ethnicities. In logistic regression, the prevalence of breastfeeding within one hour was lower in Tay-Nung (OR: 0.54; 95 % CI: 0.38, 0.77) than the majority Kinh. Prevalence of exclusive breastfeeding under 6 months was 18, 10, 17, and 33 % in Kinh, Thai-Muong, Tay-Nung, and E De-Mnong, respectively; compared to the majority Kinh, the prevalence was lower in Thai-Muong (OR: 0.42; 95 % CI: 0.25, 0.71) and higher in E De-Mnong (OR: 1.99; 95 % CI: 1.04, 3.82). Overall prevalence of bottle feeding in Thai-Muong and E De-Mnong (~20 %) was lower than in Kinh (~33 %): Thai-Muong (OR: 0.50; 95 % CI: 0.37, 0.68) and E De-Mnong (OR: 0.69; 95 % CI: 0.50, 0.95). Compared with Kinh (75 %), fewer ethnic minority children received minimum acceptable diets (33 % in Thai-Muong, 46 % in E De-Mnong, and 52 % in Tay-Nung; P < 0.05). Prevalence of minimum acceptable diet (met both dietary frequency and diversity) was lower in Thai-Muong (OR: 0.23; 95 % CI: 0.11, 0.46), Tay-Nung (OR: 0.52; 95 % CI: 0.39, 0.69), and E De-Mnong (OR: 0.55; 95 % CI: 0.33, 0.89) than the majority Kinh. Breastfeeding practices were suboptimal and differed by ethnicity, which suggests need for tailored interventions at multiple levels to address ethnic-specific challenges and norms. Complementary feeding practices were less optimal among ethnic minorities compared to Kinh, which suggests need for broad intervention including improved food availability, accessibility, and security.